Has Increasing Penalties for Teachers Achieved the Goal of Protecting Children? - Katmini, Esmeralda; Hutabarat, Rugun Romaida (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Cases of child molestation involving teachers have increased, raising serious concerns regarding the effectiveness of Indonesia’s child protection system. As individuals who occupy positions of authority that may be misused, teachers’ criminal liability requires a focused analysis within the framework of Indonesian criminal law. This study examines the forms of criminal liability applicable to teachers who commit child molestation by analyzing the elements of the offense, the principle of culpability, and the scope of their legal responsibility. It also evaluates the implementation of enhanced penalties under Law No. 35 of 2014 and Law No. 17 of 2016, which classify power imbalances as an aggravating factor. Employing a normative juridical method with statutory, conceptual, and case-based approaches, the study finds that teachers possess full legal capacity and that enhanced penalties are consistently imposed, as power relations are deemed to intensify victimization. In conclusion, the normative foundation for imposing criminal liability and enhanced penalties on teachers who commit child molestation is strong, although greater consistency in application remains necessary.